Livestock Health and Food Chain Risk Assessment. (27th August 2018) - ,; Condoleo, R; Gale, P; Adkin, A; Roberts, H; Simons, R
Abstract: The EUFORA fellowship programme 'Livestock Health and Food Chain Risk Assessment' was proposed by the Animal and Plant Health Agency (APHA), a British governmental institution responsible for safeguarding animal and plant health in the UK. The working programme, which was organised into four different modules, covered a wide range of aspects related to risk assessment including identification of emerging risks, risk prioritisation methods, scanning surveillance, food production exposure assessment and import risk assessment of animal and human infectious diseases. Over the course of the year, the Fellow had the opportunity to work for international projects with experts in these disciplines. This allowed for significant opportunities to 'learn‐by‐doing' the methods and the techniques that are employed to assess animal health and food safety risks. Moreover, he consolidated his knowledge by attending several training courses and academic lessons, submitting scientific papers to peer‐reviewed journals and conferences, giving presentations and using modelling software.